THE SPECTROPHOTOMETRIC STAR CATALOGUE - Komarov, N. S.; Dragunova, A. V.; Belik, S. I.; Karamysh, V. F.; Zakozhurnikova, N. N.; Orlova, L. F.; Kantsen, L. E.; Cherkass, A. G.; Depenchuk, E. A.; Shevchuk, T. V.; Golubovskij, V. V. (Одеські астрономічні публікації, 2017)
The spectral energy distributions for 555 stars are given. The data were obtained using the averaging procedure on the base of 20 original catalogues made by the several scientific groups